Integration of Circular Economy Principles in Consumer Behaviour for Electrical and Electronic Equipment - Nicolae Istudor; Ionel Dumitru; Alina Filip; Alin Stancu; Mihai Ioan Roșca; Andrei Canda (Amfiteatru Economic, 2023)
The electrical and electronic equipment market (EEE) is a growing one due to technological developments and innovation. The present paper captures the consumer behaviour regarding the purchase, use, and disposal of these types of equipment in the light of the transition to a circular economy. To illustrate consumer perception and attitudes towards EEE products, we conducted quantitative marketing research on a sample of 1005 urban respondents, representative by gender, age, and size of locality of residence. The research results show a rather rational consumer profile in relation to EEE products, but depending on the category of equipment, their involvement in repair, recycling, or reuse actions is different. There is also a relatively low willingness of Romanian consumers to access second-hand EEE products. The article proves its utility by proposing a set of measures to improve the circularity of EEE products, in which both EEE producers and consumers actively participate.
Keywords: M30; Q56; 330; Circular economy; marketing research; consumer behaviour; electrical and electronic equipment; repair; reuse; disposal.